Moralized memory: binding values predict inflated estimates of the group's historical influence. Issue 8 (14th September 2019) - Churchill, Luke; Yamashiro, Jeremy K.; Roediger, Henry L.
ABSTRACT: Collective memories are memories or historical knowledge shared by individual group members, which shape their collective identity. Ingroup inflation, which has previously also been referred to as national narcissism or state narcissism, is the finding that group members judge their own group to have been significantly more historically influential than do people from outside the group. We examined the role of moral motivations in this biased remembering. A sample of 2118 participants, on average 42 from each state of the United States, rated their home state's contribution to U.S. history, as well as that of ten other states randomly selected. We demonstrated an ingroup inflation effect in estimates of the group's historical influence. Participants' endorsement of binding values – loyalty, authority, and sanctity, but particularly loyalty – positively predicted the size of this effect. Endorsement of individuating values – care and fairness – did not predict collective narcissism. Moral motives may shape biases in collective remembering.